Aesthetic Experience as a Spiritual Support of Homo Post-Secularis - Byčkov, Viktor Vasilʹevič (Religions, 2019)
The essay begins with an analysis of the cultural situation of humanity after its transition to secular mentality and a gradual disenchantment with secularism, which leads to the formation of post-secular mentality. It further suggests that aesthetic experience traditionally served as a bridge between the secular and the religious/spiritual and can serve in this capacity again in the post-secular age. It outlines the main traits of the post-secular person (homo post-saecularis). Two aspects of aesthetic experience are emphasized: its in-depth penetration into nature in an attempt to achieve unity with it, and the aesthetic observation of artworks. In pursuing both of these aspects, the post-secular person attempts, just as Romantics and Symbolists previously, to grasp something invisible beyond visible forms and escape from banal reality into higher spiritual realms of being, ultimately experiencing him- or herself as having a place in the universe. Aesthetic experience, if it is correctly understood and practiced, can give all this to the present-day post-secular person. The rest of the essay is devoted to a brief history of twentieth-century views of art, mainly in French and Russian thought, that foreshadow its post-secular role, and to the author's authentic theoretical framework for understanding art and aesthetic experience, as well as his, equally authentic, program of how to achieve the post-secular function of art in practice for a present-day person.